Interactive Technologies in Participatory Planning: A Guide for Somerville Community Corporation. - Chin, Jennifer.; Dinshaw, Ayesha.; Likuski, Andy.; McBrayer, Markie.; Monty, Jay. (Tufts University. Tisch Library., 2018)
2010 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Somerville Community Corp.